Association between clinical specialty setting and disease management in patients with psoriatic arthritis: results from LOOP, a cross‐sectional, multi‐country, observational study. (6th March 2020) - Boehncke, W.H.; Horváth, R.; Dalkiliç, E.; Lima, S.A.L.; Okada, M.; Hojnik, M.; Ganz, F.; Lubrano, E.
Abstract: Background: Psoriatic arthritis (PsA) is a chronic and debilitating disease that can be managed by different clinical specialists. Objectives: The objective of the LOOP study was to evaluate the impact of clinical specialty setting on the time to diagnosis and treatment of patients with PsA. Clinical disease activity and disease burden were also compared between clinical settings. Methods: LOOP was a cross‐sectional, multicentre, observational study conducted in 17 countries in Western and Eastern Europe, the Middle East, Latin America and Asia. Adult patients (≥18 years) with a suspected or established diagnosis of PsA who were routinely visiting a rheumatologist, dermatologist or non‐rheumatology/non‐dermatology physician were enrolled. All patients were assessed by both a rheumatologist and a dermatologist. Results: Of 1483 enrolled patients, a total of 1273 had a confirmed diagnosis of PsA. There was no significant difference in the median time from onset of inflammatory musculoskeletal symptoms to PsA diagnosis between patients enrolled by rheumatologists and dermatologists (6.0 vs. 3.9 months). However, the median time from diagnosis to first treatment with a conventional synthetic disease‐modifying anti‐rheumatic drug (csDMARD) was significantly shorter in the rheumatology setting compared with the dermatology setting (0 vs. 2.0 months; P < 0.001). In addition, disease activity was significantly higher in the dermatology setting compared with the rheumatology setting. Conclusions: Differences in the management and clinical status of patients with PsA were observed between the rheumatology and dermatology settings. Importantly, median time from diagnosis to first csDMARD was significantly shorter in the rheumatology setting, and patients in the dermatology setting had higher disease activity. These data show the importance of improved collaboration between rheumatologists and dermatologists.